Canadian model of the system of health protection: basic approaches and mechanisms of realization - Makukh-Fedorkova, Ivanna (Mediaforum : Analytics, Forecasts, Information Management, 2018)
The features of forming and development the system of health protection Canada open up in this article; attention is concentrated on the personal touches and general principles of construction of sphere of medical service. An author marks that the Canadian system of health protection in obedience to international standards provides the high enough level of medical service and by a certificate there are high life-span and low level of child’s death rate it. Principles of social organization of society and system of health protection in Canada were formed in the second half of ХХ century. The system of health protection Canada has a reasonable legislative base; her forming took place in a few stages: on the first stage (beginning of 40th of XX of century) the grant of having special purpose subsidies is legislatively envisaged for the special programs of health protection and for building of hospital establishments. Such normatively-legal base assisted to development of network of hospital establishments in a country; on the second stage (in 1957) was passed an act that fastened federally-provincial allocation of financial resources on Medicare about medical insurance. Thus the quality indexes of grant of Medicare were determined by national requirements; on the third stage (1968-1979) legislative documents that formed the Canadian system of medical insurance of Medicare and set distribution of money on hospital. In 1984 in Canada was passed an act about a health protection that fastened basic principles of Medicare. This system provides free or practically free medical service and medical services to all citizens of Canada. Such structure was worked out because medical service is in the department of local, provincial authorities, but not federal government. It is well-proven that the Canadian system of health protection has certain defects also, in fact on the modern stage Canadian medicine tests a sharp requirement in experience doctors, and also one of basic problems there are large turns in medical establishments and protracted expectation of possibility to get medicare. In the same time, without regard to the outlined problems, the Canadian system of medicine under the name of Medicare is pride of country, as financed by the state and provides free medical service to all citizens practically.